Penguatan Peran Jabatan Fungsional Analis Kebijakan Untuk Menciptakan Kualitas Kebijakan Publik di Pemerintah Daerah - Delly Maulana (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2024)
This research aims to illustrate the importance of the Functional Position of Policy Analyst (JFAK) to improve the quality of public policy, both in the central and local governments. Because, in fact, public policy must prioritize real evidence, which is in accordance with the needs of the community and is the result of the best recommendations through a rational analysis process. The method used is a descriptive qualitative method using Atlas Ti software. The results of the study show how important the role of JFAK is to improve policy quality. However, its role must be strengthened, both through policy and from its authority. Therefore, there are several recommendations that must be made, namely: First, strengthening the role of JFAK through policy and authority; Second, increasing the competence of JFAK so that it has maximum competence in conducting policy analysis; and Third, forming forums so that JFAK gets maximum space to take part in carrying out its duties and functions as a policy analyst.